Studies on bacterial WILT I. inheritance of resistance to Pseudomonas solanacearum in tomato - Graham, K. M.; Yap, T. C. (Faculty of Agriculture, University of Malaya, 1976)
Variance component analysis of the PI,P2,F1 ,F2,B1,B2 generations of a cross between resis- tant (V-4) and susceptible (Walter)tomato cultivars indicated a narrow-sense heritability of wilt resistance of 42% and a broad-sense heritability of 53%, with a degree of dominance of 75%. A diallel cross was performed among six tomato cultivars, Walter, CRA-66, H-7741, Venus, VC-4 and Llanos de Colee, representing a range of susceptibility/resistance of 99.5 to 20.8 on a disease resistance scale. The results indicated that general combining ability (GCA) was considerably more important than specific combining ability (SCA), suggesting that inheri- tance of wilt resistance was due mainly to additive gene action. Among the six cultivars, Llanos de Colee, VC-4 and Venus showedgood GCA. Wilt resistance could attain a high level in a breeding procedure of repeated selfing and sel- ection, followed by intercrossing of resistant selections.